2022
DOI: 10.1039/d1cy01626a
|View full text |Cite
|
Sign up to set email alerts
|

Additive-free selective methylation of secondary amines with formic acid over a Pd/In2O3 catalyst

Abstract: Formic acid is used as the sole carbon and hydrogen source in the methylation of aromatic and aliphatic amines to methylamines. The reaction proceeds via a formylation/transfer hydrogenation pathway over...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Formic acid is likely formed upon hydrolysis of silylformate, thus indicating that in the presence of the Mn(I) catalysts used in this work, the formation of the products proceed via the silylformate route, as previously reported by Cantat and Beller [7,8] . Moreover, it has also been reported that N‐ formylation and N‐ methylation of amines can be performed by reacting the amine with formic acid and hydrosilanes in the presence of a catalyst [42–44] . This possibility was evaluated also in our catalytic system.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Formic acid is likely formed upon hydrolysis of silylformate, thus indicating that in the presence of the Mn(I) catalysts used in this work, the formation of the products proceed via the silylformate route, as previously reported by Cantat and Beller [7,8] . Moreover, it has also been reported that N‐ formylation and N‐ methylation of amines can be performed by reacting the amine with formic acid and hydrosilanes in the presence of a catalyst [42–44] . This possibility was evaluated also in our catalytic system.…”
Section: Resultssupporting
confidence: 67%
“…[7,8] Moreover, it has also been reported that N-formylation and N-methylation of amines can be performed by reacting the amine with formic acid and hydrosilanes in the presence of a catalyst. [42][43][44] This possibility was evaluated also in our catalytic system. As shown in Scheme 4, the reaction of N-ethylaniline with formic acid, in the presence of PhSiH 3 and 2 a (5 mol %) at 100 °C leads to the complete substrate conversion, with the formation of 5 a and 6 a in a 3/2 ratio.…”
Section: Catalytic Results In the Reductive Formylation/methylation O...mentioning
confidence: 99%
“…[19] In a previous paper, we reported on the additive-free, one-pot methylation of secondary amines with formic acid as the sole carbon and hydrogen source and a Pd/In2O3 catalyst. [20] In an attempt to expand the use of formic acid as a renewable methylation reagent, it was important to test whether our catalytic system could promote methylation of more challenging substrates, like primary amides, which are less nucleophilic than amines. An additional difficulty in using formic acid for the methylation of amides is to prevent the reduction of the amide function under reducing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhu et al established a homogeneous cobalt-catalyzed reductive N-formylation of amines using formic acid. Moreover, catalysts based on metallic oxide, Co@C–N, Pd/In 2 O 3 , and ionic liquids have been developed for this reaction. Despite these advancements, there are only a few examples of synthesizing formamide with formic acid as the carbonyl source, and most of these reactions still necessitate the preparation of additional catalysts (Figure d).…”
mentioning
confidence: 99%
“…Based on the results of controlled experiments and previous research, a possible reaction mechanism has been proposed (Scheme ). Initially, the lone pair on the N atoms of aniline attacks the activated C atom of HCOOH, producing formate, which then dehydrates to yield the corresponding formamide.…”
mentioning
confidence: 99%